Adolescent pregnancy: a community engaged participatory approach to design and implement an educational intervention - Siruma, Amanda Tatenda (Rhodes University, Faculty of Pharmacy, Pharmacy, 2014)
Millennium Development Goal (MDG) 5 focuses on improving maternal health, due to global acknowledgment that no woman should have to die as a result of complications during pregnancy and childbirth. Adolescents have an increased risk of maternal death compared with older women. Adolescent pregnancy also poses a threat to the empowerment of young girls by mitigating their physical, educational, social, and economic development. In this context, maternal health promotion strategies which inclusively target adolescents are crucial, not only in improving maternal health outcomes, but also in optimising the overall transition of adolescent girls to adulthood. This study was a first time collaborative partnership of the Faculty of Pharmacy and Community Engagement Office of Rhodes University with the Angus Gillis Foundation (a non-profit community development organisation), and community participants of Glenmore and Ndwayana, two rural communities in the Eastern Cape. The aim of this study was to identify the maternal health issue of most concern to community participants and to design and implement an appropriate educational intervention for a suitable target group. During the baseline phase of this study, ten focus group discussions (FGDs) were conducted with 76 community stakeholders. Semi-structured interviews (SSIs) were conducted with two Sisters-in-Charge from each Primary Health Care (PHC) facility in the study setting. Data on the stock status of World Health Organization (WHO) identified lifesaving priority medicines for women's health was also collected at both PHCs. Thereafter, pre- and posteducational interventions SSIs with female adolescent participants were conducted. The educational intervention was followed up with the development of a booklet on reproductive health. FGD participants identified adolescent pregnancy as the maternal health issue of most concern. They also highlighted challenges in service delivery of ambulance services for expectant mothers in urgent need of transportation to a referral hospital. A majority of preintervention SSI participants indicated coercion from both younger and older men as a factor influencing early sexual debut amongst adolescent girls in their communities. Despite availability in the PHCs, challenges in accessing contraceptives were highlighted by the participants. Additionally, a number of sexually active adolescent girls defaulted on their next allocated visit to the PHC due to myths regarding use of oral and injectable contraceptives. During the educational intervention sessions, participants recognised knowledge gaps regarding reproductive health issues and the influence of peer pressure as constraining factors in preventing adolescent pregnancy. During the post-intervention phase, participants highlighted that the educational intervention of this study had provided a forum to discuss ways of preventing adolescent pregnancy. The educational booklet developed is intended to serve as a resource tool of the educational programme on prevention of adolescent pregnancy, which is expected to be incorporated into the Angus Gillis Foundation's existing 'Positive Health' Programme. The results of this study show that community-based participatory research facilitated the identification of the maternal health issue of most concern to these communities. Working synergistically with key stakeholders in designing and implementing an educational intervention for preventing adolescent pregnancy provides a good foundation for future up scaling and sustainability of this educational programme.
Keywords: Uncatalogued